Dampak Kuota Gender Dalam Keterwakilan Politik: Analisis Kasus Kuota 30% Untuk Perempuan Di Parlemen Indonesia - Cahyowirawan, Angelica Maria Diahlaksmita; Maulana, Ilham; Denisnawa, Fahdy Ahmada; Ummah, Aniqotul (Peneliti.net, 2025)
This research explores the impact of the 30% gender quota for women in the Indonesian Parliament on women's political representation and the effectiveness of advocacy on gender issues. Using a qualitative approach, this research combines literature study and focus group discussions (FGD) to analyze the extent to which gender quotas have succeeded in increasing women's involvement in political decision making. The findings of this research show that although gender quotas increase the number of women in parliament, their effectiveness in influencing policies that impact women remains limited. Structural barriers and patriarchal political culture often prevent women from becoming agents of significant change. This research makes an important contribution to the literature on women's political representation in Indonesia by highlighting the challenges and opportunities in implementing gender quotas. Thus, it is hoped that this research can provide insight into the development of more inclusive and effective policies to strengthen women's advocacy in politics.